Analisis Sentimen Tentang Rencana Penghapusan Daya Listrik 450 Va Menjadi 900 Va Oleh Pemerintah Menggunakan Algoritma K-Nearest Neighbors - Fentri Boy Pasaribu; Thania Abulide; Imam Santoso (Fakultas Teknik Universitas Persada Indonesia YAI, 2023)
The 450 VA electricity owned by the State Electricity Company is electricity that has a price subsidy from the Indonesian government. 450 VA Electric Power for homes requires an MCB of 2 Ampere. For Subsidized 450 VA Home Customers Rp. 415/kWh. The 450 VA Electric Power Token has a limit of 324 kWh and if it has exceeded the maximum limit it will be rejected or fail. The government plans to eliminate the 450 VA customer class by increasing the power to 900 VA, which may not significantly increase the absorption of excess electricity supply from PT Perusahaan Listrik Negara (Persero) or PLN. The purpose of this study is to be able to analyze public opinion which can later be classified by the K-Nearest Neighbors method, then the results of the classification are 2 negative and positive classes. The research method used is data collection, data cleaning, and classification. The sentiment analysis performance results use the K-Nearest Neighbors algorithm with an accuracy rate of 86.70%.